Off-grid rural electrification planning in Sub-Saharan Africa using renewable energy systems: the case of photovoltaics in the Republic of Djibouti - (:unkn) unknown (My University, 2014)
Over the past 40 years, growth of renewable energies benefited of the new world energy frame, which resulted of the questioning about what development of human societies had to be. Furthermore, although human development comes with electricity, the rural condition of many populations of Sub-Saharan Africa incites us to look for suitable power supply alternatives. Eventually, in this specific context, renewable energies can represent a reliable solution to the off-grid electrification of rural people. However, this solution has to be economical and technical, and not only political. The Republic of Djibouti is a little developing country located in the Horn of Africa which perfectly symbolizes the social and energy challenges of rural populations in Sub-Saharan Africa. Instability and limitation of the existing electrical grid, fuel cost and lack of fossil resources point to the geographically diffused solar resource as probably the best way to improve human development and reduce poverty of Djiboutian rural peoples. Therefore, we have considered the study of photovoltaic (PV) systems within the rural off-grid electrification frame. Essentially, within this work, Djibouti was the study case of an overall scientific methodology, whose primary objective is to be reusable by countries showing similar energy and social characteristics. Firstly, in order to evaluate relevance of these systems, it was necessary to estimate the level and repartition of the solar resource across the country. So we developed a solar atlas, i.e. cartography of the hourly solar irradiation reaching the ground, based on satellite-derived irradiance estimates retrieved between 2008 and 2011. For assessing the atlas quality, we compared irradiation estimates against ground measures retrieved on 4 different sites by 2 temporary weather stations deployed between 2010 and 2013. This comparison globally showed good results with, for the daily case, a maximum relative root mean squared er
Keywords: African Research